PERAN TEKNOLOGI DIGITAL DALAM INOVASI DESAIN PEMBELAJARAN PENDIDIKAN AGAMA ISLAM DI SDN 57 TALANG SILUNGKO, BUNGO JAMBI - Adilla, Ulfa; Hendriyadi; Mabruri; Alacuba, Sovia; Ulqolbi Abdullah, Syifa (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The advancement of digital technology has precipitated profound transformations within the educational domain, particularly in Islamic Religious Education (PAI). This study aims to investigate the role of digital technology in promoting innovative instructional design for PAI curricula, thereby augmenting interactivity, effectiveness, and congruence with the needs of learners in the contemporary digital era. Utilizing a descriptive qualitative methodology, data were collected through observational methods, in-depth interviews, and documentary analysis. The findings indicate that the integration of digital technologies, including online learning platforms, interactive quiz applications, and audiovisual materials, enhances student motivation, encourages active participation, and facilitates a deeper understanding of religious doctrines. Moreover, digital technology enables PAI educators to develop more varied, collaborative, and learner-centered instructional strategies. This research seeks to propel the development of innovative and adaptable PAI learning frameworks aligned with current educational demands